Analisis SWOT Penyelenggaraan Pembelajaran Jarak Jauh dan Produktivitas Pembelajaran Anak Didik selama Pandemi Covid-19 - Meinarini Catur Utami; Suci Ratnawati; Mamduh Tirmidzi (Fakultas Teknik, 2022)
Education is a basic right of every human being, especially for school-age children. When the Covid-19 pandemic hit the world, including Indonesia, since March 16, online education or called Distance Learning (PJJ) was implemented. PJJ has been running since March 2020, and PJJ continues to be improved and adjusted to the PJJ policy from the education-related office. Researchers are interested in conducting research using observation and interview methods related to student learning outcomes during PJJ, whether there is a difference in learning productivity before PJJ and during PJJ, as well as wanting to know whether the implementation of PJJ is appropriate or not by using SWOT analysis (Strength, Weakness, Opportunity, Threats) . After observing and analyzing learning outcomes during PJJ, it is known that there is a tendency for student productivity from the UTS/UAS side to decrease compared to before the pandemic, while for students it tends to be slightly stable. For the task side, the productivity of students and students tends to decrease all. While the presence of students, student productivity is still good. The results of the SWOT analysis on the implementation of PJJ, the researcher proposes a thematic learning model, a personal model with the Problem Base Learning (PBL) method